Peer Group Support in Increasing Student Knowledge about Burnout Syndrome in Working on the Final Thesis Project: Peer Group Support dalam Meningkatkan Pengetahuan Mahasiswa tentang Burnout Syndrome dalam mengerjakan Tugas Akhir Skripsi (JURNAL UNEJ, 2023)
Final Projects for undergraduate students are time-consuming, requiring extra time and effort. While doing the final project, not a few students felt bored. The side effect of this boredom can result in decreased motivation and enthusiasm to do the final project. So it requires remarkable progress in dealing with this problem. One of the activities that can be carried out is to provide a support system for fellow students working on their final project. This activity occurs at least once a week while students complete their final project. The hope is that with mutual support, students will get new motivation and enthusiasm to complete their final assignments. Students participating in this program are very active and enthusiastic in carrying out this activity. Discussions with a peer support approach that encourages each other in compiling the final assignment can increase student enthusiasm in working on the last project.